E-Message Boards for Those Who Self-Injure: Implications for E-Health - Johnson, Genevieve; Zastawny, S.; Kulpa, A. (Springer, 2010)
Virtual communities for those who self-injure (SI) are increasingly popular and involve Internet communication technologies including e-message boards. The social and emotional support of an accepting virtual community may facilitate individual recovery from SI. Via self-report data, this study describes individuals who participate in virtual communities for those who SI and implications for e-health communities. Sixty-seven individuals who participate in virtual communities responded to ten open-ended questionnaire items posted on two e-message boards for those who SI. Participants reported a variety of strategies of self-harm. The majority indicated that they SI in response to emotional distress. Almost half reported visiting the boards at least once a day. More than half indicated that their SI decreased in frequency since joining virtual communities. Virtual communities for those who SI provide information on recovery, emotional support, and a sense of community to individuals isolated by their behavior. Improved community e-health services may include peer-to-peer online support.